Limits of Education Policy Implementation: The Attitudes of Education Stakeholders in Lithuania - Katiliūtė, Eglė (Acta Paedagogica Vilnensia, 2006)
The article deals with solving the research problem focused on the following questions: What kind of policy implementation tendencies exist in the intended level of education policy? What kind of attitudes to limits of education policy implementation exists in the reality (in-use) level of education policy among the education stakeholders (principals, head teachers, teachers, pupils, parents and students)? The research questions mentioned above are answered by three sections: the first illuminates the changes in education policy in Lithuania with the focus on policy tendencies that are performed in secondary school; the second section presents research methodology and the third part presents the generalization of research results.
Keywords: education policy; education system; strategy; education stakeholders